Group-based quantitative structure-activity relationship (G-QSAR) analysis and molecular docking of B-cell lymphoma two (BCL-2) inhibitors - Abdul Samat, Nadia Hanis; Mohamed, Farahidah; Abdullahi , Abubakar (Akademi Sains Malaysia and Confederation of Scientific & Technological Association in Malaysia (COSTAM), 2013)
Bcl-2 is the founding protein of Bcl-2 family and it is one of the inner mitochondrial membrane protein which acts as inhibitor of apoptosis, prolong cell survivals and regulate cell death negatively. Bcl-2 has been reported by previous study that it has significant percentage to be presented in many cancer cases. Classes of small molecules have been used successfully to targets Bcl-2 and in order to improve the biological activities of these anti- Bcl-2 agents various QSAR methods have been employed. In this study, an advanced method in computational drug design Group-based Quantity Structural Activity Relationship (G- QSAR) were performed using V-LIFE® on dataset of non-congeneric compounds with binding activity (IC50 range 0.003 to 400μM) available in BindingDatabase from various literatures to generate potential Bcl-2 inhibitors. The compounds were filtered based on the size which is less than 500Da where training and test set were generated using sphere exclusion approach. Simulated annealing method was used for variables selection and 616 two dimensional descriptors were calculated. Multiple regression model building was used and the best model obtained has the value of r2: 0.8345, q2: 0.7455, predictive r2: 0.8164 and best rand r2: 0.2181 which then used to generate new compounds candidates virtually. Newly generated compounds were analysed through activity predictions and docking into the available Bcl-2 crystal structures from PDB using Glide® and Prime®. All results would be presented and discussed.